Phylogeny of Lithobiidae Newport, 1844, with emphasis on the megadiverse genus Lithobius Leach, 1814 (Myriapoda, Chilopoda) - Ganske A; Vahtera V; Dányi L; Edgecombe GD; Akkari N (Wiley-Blackwell Publishing Ltd., 2022)
Abstract Phylogenetic analyses based on molecular and morphological data were conducted to shed light on relationships within the mostly Palaearctic/Oriental centipede family Lithobiidae, with a particular focus on the Palaearctic genus Lithobius Leach, 1814 (Lithobiidae, Lithobiomorpha), which contains >500 species and subspecies. Previous studies based on morphological data resolved Lithobius as nonmonophyletic, but molecular-based phylogenetic analyses have until now sampled few species. To elucidate species inter-relationships of the genus, test the validity of its classification into subgenera, and infer its relationships with other Lithobiidae, we obtained molecular data (nuclear markers: 18S rRNA, 28S rRNA; mitochondrial markers: 16S rRNA, COI) and 61 morphological characters for 44 species of Lithobius representing four of its eight subgenera and nine other representatives of Lithobiidae. The data were analyzed phylogenetically using maximum-likelihood, parsimony and Bayesian inference. This study suggests that (i) a close relationship between L. giganteus and the pterygotergine Disphaerobius loricatus highlighted in recent morphological analyses is also strongly supported by molecular data, and Pterygoterginae is formally synonymized with Lithobiinae; (ii) the Oriental/Australian genus Australobius is consistently resolved as sister group to all other sampled Lithobiidae by the molecular and combined data; (iii) the subfamily Ethopolyinae may be paraphyletic; (iv) the genus Lithobius is nonmonophyletic; (v) the subgenera Lithobius, Sigibius and Monotarsobius are nonmonophyletic and should not be used in future taxonomic studies; and (vi) there are instances of cryptic species and cases in which subspecies should be elevated to full species status, as identified for some European taxa within Lithobius.